GENERATION AND CHARACTERIZATION OF GENETIC REASSORTANTS BETWEEN POTENTIALLY PANDEMIC VIRUSES (A/H9N2 OR A/H5N8) AND THE A/HONG KONG/1/68/162/35 (H3N2) MASTER DONOR VIRUS - V. I. Grishchenko (Sankt-Peterburg : NIIÈM imeni Pastera, 2018)
.